Experimental study of the photovoltaic module deterioration in the extreme weather desert environment of Adrar - LARIBI Slimane; GHAITAOUI Touhami; ARAMA Fatima Zohra; HAMOUDA Messaoud (university Of Eloued جامعة الوادي, 2020)
The degradation of the electrical performance of photovoltaic panels UDTS 50W exposed to the sun for a long period of about 10 years in a Saharan environment of Adrar was presented. In this article, we will present some experimental results obtained during the analysis of the I-V characteristics of some UDTS 50W photovoltaic panels tested in the real conditions of the Saharan environment (Adrar region). The degradation of the electrical performance of the UDTS-50 W module is visualized through the analysis of the I-V and P-V characteristics experimentally or by visual field inspection of a renewable energy research unit in a Saharan environment. The physical parameters of the equation governing these characteristics were determined by the effective iteration method using only the information in the data sheet. The comparison between the experimental characteristic curves IV and PV of the PV modules (UDTS 50) and the reference in STC shows that the degradation of the electrical performances are due globally by the delamination and the discoloration of the EVA encapsulate after the long term exposure in a desert environment
Intervention
Keywords: Degradation; Photovoltaic panels; UDTS-50W; electrical performance